Edukasi dan Peningkatan Kualitas Pengelolaan Obat di Rumah Tangga: Studi Kasus di Dusun Sidasari Wetan Desa Kubangkangkung Kawunganten Cilacap (Education and Quality Improvement of Drug Management in Family: A Case Study at Dusun Sidasari Wetan, Kubang - Wasito, Hendri; Pratiwi, Hening; Wibowo, Adi; Solihat, Nia Kurnia (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Drugs are an important component of health services that are the needs of the community. There is still a lack ofcommunity knowledge of medicines and management especially for family members, hence an educational effort as well asimprovement of quality of drug management in family through training program and mentoring by pharmacist. Thiscommunity service activity aims to determine the knowledge and attitude of the community in managing drugs in the familyand improve the quality of drug management by the community in the family. The activity was conducted in SidasariWetanKubangkangkung Village Kawunganten Cilacap. The workshop on drug management in family was conducted by pharmaciststo the 33 participants. Data collection was done by using questionnaire and observation through home visit. The result of theactivity shows that the increase of knowledge and attitude of the society in managing drugs in the familywere 10% and 7%,respectively. Workshop activities and mentoring by pharmacists can provide benefits and behavioral changes in family drugsmanagement.